Emerging tribal image - Doshi, S. L. (Shambu Lal). author (Jaipur : Rawat Publications, 1997)
With reference to Rajasthan, India.
Includes bibliographical references and index.
Keywords: SOCIAL CHANGE -- INDIA -- RAJASTHAN; BHIL (INDIC PEOPLE) -- RAJASTHAN; RAJASTHAN (INDIA) -- SCHEDULED TRIBES -- SOCIAL LIFE AND CUSTOMS